Career development, compensation, job security, workplace environment and employee loyalty in Isuzu Hicom (M) Sdn Bhd / Wan Muhammad Iqmal Fazri Wan Juahari - Wan Juahari, Wan Muhammad Iqmal Fazri (2019)
The purpose of this research is to examine the relationship between career development, compensation, job security, work environment and employee loyalty. Researcher also wants to know what are the most factors that contribute to the employee loyalty among the employees of Isuzu Hicom (M) Sdn Bhd. Previous study from other researchers also has been used as the evidence for each variable that have been choosing for the research. Method that has been used by the researcher is quantitative which is to gathering quantifiable data and performing statistical, mathematical or computational techniques using Statistical Package for the Social Science (SPSS). Apart from that, researcher also used Convenience Sampling for sampling techniques whereby sample size needed were presented with calculation based on Krejcie and Morgan table. Based on the result, all the independent variables have a positive relationship with employee loyalty while the most contributing is Work Environment. Finally, this study also helps the organization to overlook the mistake and overcome the mistake by using the recommendation that has been suggested